MOTIVATION TO INCREASE EIGER GRESIK EMPLOYEE LOYALTY - Ghufron, Firdaus; Azizah Salsa BellaIra Vania Putri , Nur; Ismail, Iriani (Universitas Islam Lamongan, 2024)
This study explores the role of motivation in human resource management (HRM) and its impact on employee loyalty. Human resources are a crucial element in managing and utilizing other resources effectively. Motivation greatly influences employee performance and loyalty. This study uses a qualitative descriptive method with a literature review to examine how motivation is implemented and its effects on loyalty. Effective motivation can increase employee loyalty through a supportive work environment and strong leadership, although challenges such as the gap between theory and practice and less supportive leadership can hinder its implementation.